2022
DOI: 10.3390/ijerph191711063
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Hybrid Exercise Program on the Physical Fitness of Frail Elderly

Abstract: Background: Frailty is a serious physical disorder affecting the elderly all over the world. However, the frail elderly have low physical fitness, which limits the effectiveness of current exercise programs. Inspired by this, we attempted to integrate Baduanjin and strength and endurance exercises into an exercise program to improve the physical fitness and alleviate frailty among the elderly. Additionally, to achieve the goals of personalized medicine, machine learning simulations were performed to predict po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…These findings indicate that Taichi exercise has a significant effect in improving physical functional capacity in older adults, with a positive impact on TUGT perfor- mance. A systematic review conducted by Wang [ 11 ] gathered a substantial amount of empirical evidence to evaluate the effectiveness of exercise based on traditional Chinese medicine. The quantitative analysis revealed that the Taichi group demonstrated a reduction of 2.62 s in the TUGT compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that Taichi exercise has a significant effect in improving physical functional capacity in older adults, with a positive impact on TUGT perfor- mance. A systematic review conducted by Wang [ 11 ] gathered a substantial amount of empirical evidence to evaluate the effectiveness of exercise based on traditional Chinese medicine. The quantitative analysis revealed that the Taichi group demonstrated a reduction of 2.62 s in the TUGT compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines of the Asian Working Group for sarcopenia [ 3 ], the task force of the International Conference on sarcopenia and Frailty Research [ 4 ], and the Singapore Society for Geriatric Medicine [ 5 ] all strongly endorse exercise training as the first-line therapy for the management of sarcopenia. Exercise programs, in particular, represent a crucial component of rehabilitation and have been shown to have a favorable impact on sarcopenia [ 6 11 ], the implementation of Chinese traditional exercise resulted in a 27.8% reverse in sarcopenia [ 12 ]. Despite the known benefits, participation in and adherence to exercise training among older adults with chronic musculoskeletal conditions are even lower than among the general old population [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%